Methodological Approaches to Evaluation and Analysis of Labor Efficiency in the Spheres of Fuel and Energy Complex - VANCHUKHINA, Lyubov I.; LEYBERT, Tatyana B.; KHALIKOVA, Elvira A. (Journal of Environmental Management and Tourism, 2017)
The article is devoted to the issues of methodological approaches to evaluation of labor efficiency in the spheres of fuel and energy complex of Russia and to the analysis of factors that influence its level. Special attention is paid to domestic and foreign approaches to quantitative evaluation of labor efficiency, used not only for a specific enterprise but for determination of its level on the whole for the groups of enterprises and spheres of industry. The authors systematize the traditional methods of evaluation of labor efficiency in view of sectorial specifics of functioning of the spheres of fuel and energy complex of Russia. Mathematical models of factor analysis of labor efficiency in the spheres of fuel and energy complex are developed which allow evaluating the influence of effectiveness of use of main capital and investment activity of enterprises.